Media coverage of harm reduction, 2000–2016: A content analysis of tone, topics, and interventions in Canadian print news. (1st December 2019) - Cameron Wild, T.; Koziel, Jakob; Anderson-Baron, Jalene; Hathaway, Josh; McCurdy, Ashley; Xu, Xin; Asbridge, Mark; Belle-Isle, Lynne; Hathaway, Andrew; MacPherson, Donald; Hyshka, Elaine
Highlights: Media coverage shapes and reflects views on contentious harm reduction services. Canadian newspapers rarely described harm reduction negatively or emphasized crime. Coverage of supervised drug consumption dominated other harm reduction services. This may have undermined public support for a spectrum of harm reduction services. Abstract: Background: Harm reduction interventions reduce mortality and morbidity for people who use drugs (PWUD), but are contentious and haphazardly implemented. This study describes volume and content of Canadian newspaper coverage of harm reduction produced from 2000 to 2016. Methods: Searches of 54 English-language newspapers identified 5681 texts, coded for type (news reports, opinion pieces), tone (positive, negative, or neutral/balanced coverage), topic (health, crime, social welfare, and political perspectives on harm reduction), and seven harm reduction interventions. Results: Volume of coverage doubled in 2008 (after removal of harm reduction from federal drug policy and legal challenges to Vancouver's supervised consumption program) and quadrupled in 2016 (tracking Canada's opioid emergency). Health perspectives on harm reduction were most common (39% of texts) while criminal perspectives were rare (3%). Negative coverage was over 10 times more common in opinion pieces (31%) compared to news reports (3%); this trend was more pronounced in British Columbia and Alberta, a region particularly affected by Canada's opioid emergency. Supervised drug consumption accounted for 49% of all newspaper coverage. Conclusions: Although federal policy support for harm reduction waxed and waned over 17 years, Canadian newspapers independently shaped public discourse, frequently characterizing harm reduction positively/neutrally and from a health perspective. However, issue framing and agenda setting was also evident: supervised drug consumption offered in a single Canadian city crowded out coverage of all other harm reduction services, except for naloxone. This narrow sense of 'newsworthiness' obscured public discourse on the full spectrum of evidence-based harm reduction services that could benefit PWUD.